The Future of Rice: Viet Nam’s Million-Hectare Transformation - Nelson, Katherine; Binh Thang Cao; Thuy Anh Nguyen (World Bank, 2025)
The rice sector employs over 140 million people worldwide, with 80% of production done by small holder farmers. But it's facing a turbulence: effects of climate change, slowing yield growth, excessive water use, and high greenhouse gases emission. This episode discusses how Viet Nam is transforming its rice sector so the crop can continue to be a staple food and support those who depend on it to earn a living, while also addressing its environmental footprint.